Kaji Eksperimen Sistem Organic Rankine Cyle (ORC) Pada Temperatur Sumber Panas 95 ⁰C - Muhammad Nur Ahmad H; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
This study discusses the experiment of Organic rankine cycle (ORC) system at 95 ⁰C heat source . Organic rankine cycle is a conventional modification cycle, where ORC fuels move is organic fluid (refrigerant), which has a low boiling point, so that it produces steam only requires low temperaturs. The working fluid used is R134a obtained from the reference of previous studies. Renewable energy sources such as solar heat, geothermal energy and industrial waste heat are energy sources capable of meeting the world's electricity needs. However, the low temperatur of the heat source cannot be used as electric power, so the organic ranking cycle can be used as a renewable energy source that uses low temperatur heat. Data collected in the from temperatur, pressure and mass flow rate. From the results of the experiment, the maximum power is 305.02 Watts and the maximum efficiency is 4.29% at the turbine inlet pressure of 1.5 MPa and the turbine inlet temperatur is 67.91 ⁰C. Keywords: Organic rankine cycle, R134a, Renewable Energy.